Subclinical Mastitis and Antibiotic Resistance in Dairy Cows, Bharatpur, Nepal - Bajracharya, Anup Muni; Shrestha, Ankit; Shrestha, Anup; Pokhrel, Asmita; Pokhrel, Rojina; Gurung, Shabnam (Jana Adarsha Research Journal, 2025)
Subclinical mastitis is a significant health concern in dairy cows, leading to decreased milk production and quality. This study aimed to determine the prevalence of subclinical mastitis in lactating cows from Bharatpur Municipality, Chitwan, Nepal, and assess the antibiotic resistance patterns of pathogens isolated. A total of 200 milk samples from 50 cows (Jersey, Holstein, and crossbreeds) were tested using the California Mastitis Test (CMT), with 30 samples (15%) testing positive. The prevalence of subclinical mastitis was higher in older cows and those with higher parity, with Jersey cows showing an increasing trend from 34.62% (3-6 years) to 100% (9 years or above). Staphylococcus aureus was the most frequently isolated pathogen (53.85%), followed by Coagulase-negative Staphylococci (CONS) and Bacillus spp. The antibiotic susceptibility test revealed that Staphylococcus aureus isolates were most sensitive to gentamicin (100%), followed by doxycy¬cline and cotrimoxazole. These findings highlight the need for regular monitoring of mastitis and prudent use of antibiotics to prevent resistance.